DAMPAK DAN PENCEGAHAN COVID 19 DI MTs BANDAR AGUNG - Subagio, Toyib (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2020)
This article aims to describe the impact and prevention of Covid 19 at MTs Bandar Agung. The data collection methods used were observation, interview and documentation. The results showed that the impact of Covid 19 caused temporary closure of schools so that the learning process used an online system which resulted in the learning process being not optimal. Covid19 prevention efforts are carried out through socialization and education to students about Covid 19 as well as regular spraying of disinfectants in classrooms and teacher offices. The positive contribution of this article can provide information to the wider community about the impact and prevention of Covid 19 in particular in the realm of educational institutions.